Unraveling Electron Dynamics in p-type Indium Phosphide (100): A Time-Resolved Two-Photon Photoemission Study - Diederich, Jonathan; Velasquez Rojas, Jennifer; Zare Pour, Mohammad Amin; Ruiz Alvarado, Isaac Azahel; Paszuk, Agnieszka; Sciotto, Rachele; Höhn, Christian; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; Schmidt, Wolf Gero; Hannappel, Thomas; et al. (Journal of the American Chemical Society)

Substrate Doping and Defect Influence on P-Rich InP(001):H Surface Properties - Sciotto, Rachele; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (Surfaces)
Density-functional theory calculations on P-rich InP(001):H surfaces are presented. Depending on temperature, pressure and substrate doping, hydrogen desorption or adsorption will occur and influence the surface electronic properties. For p-doped samples, the charge transition levels of the P dangling bond defects resulting from H desorption will lead to Fermi level pinning in the lower half of the band gap. This explains recent experimental data. For n-doped substrates, H-deficient surfaces are the ground-state structure. This will lead to Fermi level pinning below the bulk conduction band minimum. Surface defects resulting from the adsorption of additional hydrogen can be expected as well, but affect the surface electronic properties less than H desorption.

Atomic wires on substrates: Physics between one and two dimensions - Pfnür, H.; Tegenkamp, C.; Sanna, S.; Jeckelmann, E.; Horn-von Hoegen, M.; Bovensiepen, U.; Esser, N.; Schmidt, Wolf Gero; Dähne, M.; Wippermann, S.; Bechstedt, F.; Bode, M.; et al. (Surface Science Reports)

Defect-Assisted Exciton Transfer across the Tetracene-Si(111):H Interface - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review Letters)

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

Interactions of polyvinyl acetate dispersions with nanostructured superhydrophilic and superhydrophobic Ti6Al4V alloy surfaces - Neßlinger, Vanessa; Atlanov, Jan; Grundmeier, Guido (Discover Applied Sciences)
Abstract Nanostructured bilayer thin films with superhydrophobic and superhydrophilic surfaces were prepared using Ti6Al4V alloy substrates which allowed for the comparative analysis of polyvinyl acetate (PVAc) particle adsorption as a function of the interface structure. The PVAc particles were obtained from emulsion polymerization of vinyl acetate. A superhydrophilic TiO 2 nanofiber-based 3D network was created on the Ti6Al4V alloy substrate by application of a hydrothermal method. Subsequent UV-grafting of ultra-thin polydimethylsiloxane (PDMS) layers resulted in a superhydrophobic surface. The modification steps were followed via Diffuse Reflectance Infrared Fourier Transform Spectroscopy, X-ray Photoelectron Spectroscopy, Field Emission-Scanning Electron Microscopy, contact angle and Electrochemical Impedance Spectroscopy. A mechanism for the adsorption of PVAc at the two electrolyte/substrate interfaces could be revealed.

Entwicklung und Validierung eines Instruments zur differenzierten Erfassung disziplinbezogener und berufsbezogener digitaler Kompetenzen von Lehrkräften in der beruflichen Bildung - Sänger, Niklas (Zeitschrift für Berufs- und Wirtschaftspädagogik)
The study validates an instrument for assessing digital competencies of teachers in vocational education, based on a TPACK extension which considers the knowledge sources of the dual subject matter. For validation, student teachers of vocational and business education in their first bachelor’s semester (n=112) were surveyed. In addition, student teachers in their first master’s semester (n=94) were surveyed to analyze the nomological validity of the instrument. The results confirm the assumed subdivision of content knowledge into the reference systems of profession and discipline. The model fit (χ2/df=1.284; RMSEA=0.051; CFI=0.948; SRMR=0.061) and the internal consistency of the scales can be rated as good. The nomological analysis of the instrument shows theoretically plausible results.

Entwicklung und Validierung eines Instruments zur differenzierten Erfassung fachlicher und berufsbezogener digitaler Kompetenzen von Lehrkräften in der beruflichen Bildung für die kaufmännische Domäne - Sänger, Niklas

Education through Entrepreneurship: Developing self-direct competencies in Higher Education - Jenert, Tobias; Büker, Ronja (EARLI SIG 4 & 17 Conference 2024)

Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber,

Perspektiven von Kindern auf den Übergang in die weiterführende Schule. Fallportrait einer Schülerin mit zugeschriebenem sonderpädagogischen Förderbedarf im Bereich Lernen. Beitrag auf der 32. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität des Saarlandes, Saarbrücken. - Büker, Petra; Herding, Jana

The impact of market concentration and market power on banking stability – evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (The Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.

The value of teaching with animals. A qualitative study of teachers’ perspectives on their animal-assisted educational work - Mombeck, Mona Maria

EXTRA: Tiergestützte Pädagogik - Mombeck, Mona Maria (Beziehung, Erziehung, Bindung: Wie Hunde sich an unserer Seite entfalten können - Forschung im Dienst des Mensch-Hund-Teams)

Soziologie des Flitzers - Riedl, Lars (Kölner Zeitschrift für Soziologie und Sozialpsychologie)

Die gesellschaftliche Bedeutung von Fußball-Großereignissen: Eine soziologische Analyse am Beispiel der UEFA EURO 2024 - Riedl, Lars (Einsichten + Perspektiven. Bayerische Zeitschrift für Politik und Geschichte)

Analyse der Analogiebildung in kontextorientierten Lernumgebungen - Wedekind, Lisa; Pollmeier, Pascal; Fechner, Sabine (Frühe naturwissenschaftliche Bildung)

Coherent Swing‐Up Excitation for Semiconductor Quantum Dots - Boos, Katarina; Sbresny, Friedrich; Kim, Sang Kyu; Kremser, Malte; Riedl, Hubert; Bopp, Frederik W.; Rauhaus, William; Scaparra, Bianca; Jöns, Klaus; Finley, Jonathan J.; Müller, Kai; Hanschke, Lukas (Advanced Quantum Technologies)
Abstract Developing coherent excitation methods for quantum emitters ensuring high brightness, optimal single‐photon purity and indistinguishability of the emitted photons has been a key challenge in the past years. While various methods have been proposed and explored, they all have specific advantages and disadvantages. This study investigates the dynamics of the recent swing‐up scheme as an excitation method for a two‐level system and its performance in single‐photon generation. By applying two far red‐detuned laser pulses, the two‐level system can be prepared in the excited state with near‐unity fidelity. The successful operation and coherent character of this technique are demonstrated using a semiconductor quantum dot (QD). Moreover, the multi‐dimensional parameter space of the two laser pulses is explored to analyze its impact on excitation fidelity. Finally, the performance of the scheme as an excitation method for generating high‐quality single photons is analyzed. The swing‐up scheme itself proves effective, exhibiting nearly perfect single‐photon purity, while the observed indistinguishability in the studied sample is limited by the influence of the inevitable high excitation powers on the semiconductor environment of the quantum dot.

Experimental measurement of the reappearance of Rabi rotations in semiconductor quantum dots - Hanschke, L.; Bracht, T. K.; Schöll, E.; Bauch, David; Berger, Eva; Kallert, Patricia; Peter, M.; Garcia, A. J.; Silva, S. F. Covre da; Manna, S.; Rastelli, A.; Schumacher, Stefan; et al. (arXiv:2409.19167)
Phonons in solid-state quantum emitters play a crucial role in their performance as photon sources in quantum technology. For resonant driving, phonons dampen the Rabi oscillations resulting in reduced preparation fidelities. The phonon spectral density, which quantifies the strength of the carrier-phonon interaction, is non-monotonous as a function of energy. As one of the most prominent consequences, this leads to the reappearance of Rabi rotations for increasing pulse power, which was theoretically predicted in Phys. Rev. Lett. 98, 227403 (2007). In this paper we present the experimental demonstration of the reappearance of Rabi rotations.

Purcell-enhanced single-photon emission from InAs/GaAs quantum dots coupled to broadband cylindrical nanocavities - Jöns, Klaus
On-chip emitters that can generate single and entangled photons are essential building blocks for developing photonic quantum information processing technologies in a scalable fashion. Semiconductor quantum dots (QDs) are attractive candidates that emit high-quality quantum states of light on demand, however at a rate limited by their spontaneous radiative lifetime. In this study, we utilize the Purcell effect to demonstrate up to a 38-fold enhancement in the emission rate of InAs QDs by coupling them to metal-clad GaAs nanopillars. These cavities, featuring a sub-wavelength mode volume of 4.5x10-4 (λ/n)3 and low quality factor of 62, enable Purcell-enhanced single-photon emission across a large bandwidth of 15 nm. The broadband nature of the cavity eliminates the need for implementing tuning mechanisms typically required to achieve QD-cavity resonance, thus relaxing fabrication constraints. Ultimately, this QD-cavity architecture represents a significant stride towards developing solid-state quantum emitters generating near-ideal single-photon states at GHz-level repetition rates.